2019
DOI: 10.1186/s13756-019-0590-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of antibiotic resistance in ESKAPE organisms: a systematic review

Abstract: Background Antibiotic resistance (ABR) is one of the biggest threats to global health. Infections by ESKAPE ( Enterococcus , S. aureus , K. pneumoniae , A. baumannii , P. aeruginosa , and E. coli ) organisms are the leading cause of healthcare-acquired infections worldwide. ABR in ESKAPE organisms is usually associated with significant hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
159
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 97 publications
(175 reference statements)
6
159
2
5
Order By: Relevance
“…The emergence of antibiotic resistance and multidrug-resistant bacteria is a growing global health concern (May, 2014;O'Neill, 2016;Suk et al, 2019;Zhen et al, 2019), and methodology to suppress the emergence of resistant bacteria is desired. Various mechanisms for antibiotic resistance have been identified, including the activation of efflux pumps, modifications of specific drug targets, and shifts in metabolic activities (Harder et al, 1981;Okusu et al, 1996;Palmer and Kishony, 2014;Toprak et al, 2011;Yelin and Kishony, 2018;Zampieri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of antibiotic resistance and multidrug-resistant bacteria is a growing global health concern (May, 2014;O'Neill, 2016;Suk et al, 2019;Zhen et al, 2019), and methodology to suppress the emergence of resistant bacteria is desired. Various mechanisms for antibiotic resistance have been identified, including the activation of efflux pumps, modifications of specific drug targets, and shifts in metabolic activities (Harder et al, 1981;Okusu et al, 1996;Palmer and Kishony, 2014;Toprak et al, 2011;Yelin and Kishony, 2018;Zampieri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Global data are alarming: drug-resistant infections are responsible for one death every 45 s in the world [13]. Besides this high increase in mortality and morbidity rates, antibiotic resistance also generates a high additional economic burden, reaching up to 20 billion dollars for the U. S. healthcare system [12,14,15].…”
Section: Eskapee Pathogenic Bacteriamentioning
confidence: 99%
“…Therefore, antibiotic resistance is one of the most serious global public health threats of the 21st century. The World Health Organization has highlighted that antibiotic resistance in clinical treatment, if left to persist at the current rate, may lead to 10 million deaths and a reduction of 2-3.5% gross domestic product annually by 2050 [2,3]. Among antibiotic resistant bacteria, "ESKAPE" pathogens, including Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species [4], cause the majority of hospital infections with higher mortality of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among antibiotic resistant bacteria, "ESKAPE" pathogens, including Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species [4], cause the majority of hospital infections with higher mortality of patients. "ESKAPE" pathogens effectively escape the effects of commonly used antibacterial drugs, and are usually associated with significantly higher economic burden by increasing the duration of hospital stays and deceasing workforce productivity [3,5]. Recently, a notable study reported that ESKAPE pathogens represented 42.2% of species isolated from bloodstream infections in the United States [5].…”
Section: Introductionmentioning
confidence: 99%